Pinna nobilis in the Greek seas (NE Mediterranean): on the brink of extinction? - MARIA ZOTOU; PAVLOS GKRANTOUNIS; ELPIDA KARADIMOU; KONSTANTINOS TSIRINTANIS; MARIA SINI; DIMITRIS POURSANIDIS; MARTA AZZOLIN; THANOS DAILIANIS; ELENI KYTINOU; YIANNIS ISSARIS; VASILIS GERAKARIS; MARIA SALOMIDI; et al. (Mediterranean Marine Science, 2020)
The Mediterranean endemic fan mussel Pinna nobilis is suffering an ongoing basin-scale mass mortality event (MME) since 2016. As most Mediterranean populations have collapsed, the species has been declared as Critically Endangered in the IUCN Red List of threatened species. In an effort to track the progress of the MME and provide updated information on the status of the species in the Greek seas, we compiled data collected through dedicated surveys and opportunistic assessments during 2019 and 2020. A total of 14589 fan mussel individuals, of which 81.1% dead, were recorded in 258 site surveys. Of the remaining 2762 live individuals, 256 were juveniles. Two marine areas which still sustain living populations were identified, namely Kalloni Gulf (Lesvos Island), and Laganas Bay (Zakynthos Island). The inner part of Kalloni Gulf appears to maintain the largest surviving population of the species in the eastern Mediterranean, with an abundance estimate of 684000 individuals (95% confidence interval: 322000-1453000). Solitary, potentially resistant, scattered individuals were recorded in several sites. Other previously abundant populations that had been assessed in the past, specifically those of Lake Vouliagmeni (Korinthiakos Gulf), Souda Bay (Crete) and Gera Gulf (Lesvos Island), and which collectively summed up to ~350,000 individuals, have now been wiped out. Our results document the collapse of most P. nobilis populations throughout the Greek seas. The MME has substantially progressed between early 2019 and mid-2020, as indicated by the increase of mortality at sites consecutively monitored multiple times. This work highlights the urgent need for continuous monitoring of surviving populations and calls for the immediate implementation of an effective protection and management strategy that will ensure the persistence of surviving individuals and the production of resistant offspring.

Presence of mycotoxins, heavy metals and nitrate residues in organic commercial cereal-based foods sold in the Greek market - Adriana Skendi; Maria Papageorgiou; Maria Irakli; Dimitris Katsantonis (Journal of Consumer Protection and Food Safety, 2020)